Combining radiation and immunotherapy for synergistic antitumor therapy - Ferrara, Theresa A. (2009)
The combination of radiation therapy and immunotherapy holds enticing promise as a strategy for cancer treatment. Preclinical studies have shown that radiation may act synergistically with immunotherapy to enhance or broaden antitumor immune responses, in part due to radiation-induced phenotypic alterations of tumor cells that render them more susceptible to immune-mediated killing. Clinical trials employing the combination of therapeutic vaccines with radiation have confirmed many of these findings, and clinical endpoint human studies are both ongoing and planned. This review examines a) the evidence that radiation induces immunologic death, b) the mechanisms by which radiation therapy can induce or augment antitumor immune responses, and c) translational studies demonstrating that immunotherapy can be effectively combined with radiation therapy. Finally, we review recent and current clinical trials combining radiation therapy with immunotherapy.